Efficiency Measurement on Banking Sector in Bangladesh - Hoque, Md. Rashedul; Rayhan, Md. Israt (Dhaka University Journal of Science, 2013)
Nowadays banking sector in Bangladesh plays a considerable role in the economic development and business improvement, in this aspect ranking of banks is vital. In this study, an attempt has been made to rank some of the Bangladeshi Banks. Also, the most efficient bank is identified here. Data Envelopment Analysis is used for this purpose. The data from the annual reports of different banks are used in this study for the purpose of efficiency checking. In Data Envelopment Analysis two types measurement techniques are used constant returns to scale and variable returns to scale. Since this study attempts to maximize output, that is, the operating profit, so the output oriented Data Envelopment Analysis is used here. The most efficient bank is identified here by the highest efficiency score obtained by that specific bank. Dhaka Univ. J. Sci. 61(1): 1-5, 2013 (January) DOI: http://dx.doi.org/10.3329/dujs.v61i1.15088